EFFECT OF CONSUMER PROTECTION FUNCTION ON FINANCIAL PERFORMANCE OF SACCOS IN KENYA - Ndungo', Jackson Mnago; Tobias, Dr. Olweny; Florence, Dr. Memba (International Journal of Finance and Accounting, 2016)
Purpose: The study sought to determine the effect of consumer protection function on financial performance of SACCOs in Kenya. Methodology: The study adopted a descriptive research design. The target population comprised of registered 181 deposit-taking SACCOs as at 31st December 2014 and the three licensed CRBs in Kenya. Stratified random sampling was used in the study, where SACCOs were grouped into five respective strata which were then randomly selected. The SACCOs were grouped into five respective strata of government based, teachers based, farmers based, private institutions based and community based. The study sampled 135 of the 181 (74.5%) licensed deposit taking SACCOs since these were the only licensed deposit-taking SACCOs by 2014. The choice of the licensed deposit taking SACCOs in Kenya was very objective since it was possible to obtain information that is representative of Kenya. In addition, SACCOs form the smaller arm in the financial sector and in most cases deals with a larger group of clients from the informal sector as opposed to other financial institutions like banks. Both primary and secondary data were analyzed using SPSS software, and statistics generated included descriptive statistics and inferential statistics. The particular descriptive statistics used included frequencies and percentages while the particular inferential statistics included Pearson correlation analysis and regression. Correlation analysis was used to establish relationships between the consumer protection function and financial performances. Regression analysis was used to establish the significance of the variables and the degree of causal effect of the independent variables on the dependent variable. The hypotheses testing were conducted using simple regression model. Findings: From the data analysis the study concluded that there was a significant and positive relationship between consumer protection function and financial performance thus the existence of credit reference bureaus was suitable for improving financial performance of SACCOs. This implies that that Credit reference bureaus have led to consumer protection and increased customers' rights. Similarly, credit reference bureaus have led to assumption that borrowing is a right regardless of capabilities. Credit reference bureaus have reduces undesired monopolistic actions of lenders. Lastly, credit reference bureaus have led to reduced bad "culture" on loan repayment. Recommendation: The study recommended that lenders should ensure that they have accurate information before listing the unworthy borrowers to avoid unnecessary legal battles which may affect performance as a measure for customer rights protection.